Social Media Strategies on Brand Awareness at a Small Business Consultancy Firm in South Africa - Rukuni, Tarisai F.; Maziriri, Eugine Tafadzwa; Mofoka, Tsepo (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Small and medium enterprises – including those in the business consultancy industry – are strategic for the development of the South African economy and for developing marginalised economies through employment creation and income generation. However, the existence of small and medium business consultancy firms is threatened by competitive pressure of multinational consulting firms such as the PricewaterhouseCoopers, McKinsey and KPMG [8]. Small and medium business consultancy firms need to adopt innovative strategies for survival. Appropriate use of social media strategies is one strategy that can be adopted by small and medium business enterprises to influence brand awareness and brand loyalty and to build a competitive edge. An inability to use social media as a business strategy results in poor brand awareness, a decrease in sales, and business closure. It is against this background that this study aimed to assess customers’ perceptions of social media strategies employed by the small and medium business consultancy firm, investigate the relationship between social media strategies and brand awareness, and evaluate the relationship between brand awareness. A quantitative descriptive research methodology, using a structured questionnaire was employed to collect data from a sample of 231 customers at the business consultancy. The Statistical Package for Social Sciences version 25 was employed to conduct descriptive and multivariate analysis, including mean, standard deviation, correlation and regression analysis. Findings indicated that customers had negative perceptions of social media strategies employed by the small and medium business consultancy firm. It was also found that social media strategies had a statistically significant positive relationship with brand awareness and brand acceptance. The research findings hold major implications for theory and practice.